SOEKARNO DAN MODERNISASI ISLAM MUHAMMADIYAH BENGKULU: SEBUAH TINJAUAN HISTORIS - Latifah, Lailatul (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2020)
Soekarno was one of the figures of the National movement that fought against the Dutch. He played a very important role in advancing the nation of Indonesia. Soekarno also joined the Sarekat Muhammadiyah. His encounter with the founder of Sarekat Muhammadiyah began when he was in Surabaya. When he was exiled to Bengkulu, the Sarekat Muhammadiyah was used as a means of fighting for the Indonesian nation. One of his role in Muhammadiyah in Bengkulu was eradicated the customs of Muhammadiyah people in putting restrictions on men and women when conducting meetings. He also established a conference of Daeratul Kubro in the Sumatra region, in addition to creating PEKOPE (War Victims Assistance) in order to welcome Japan to Japan Indonesia. This is a library research using a historical research method consisting of heuristics while the data was obtained by referring to an autiobiography of Soekarno entitled Soekarno Penyambung Lidah Rakyat Indonesia. This research found that Soekarno made some contributions to the development of Muhammadiyah in Bengkulu through initiatives that he made in efforts to struggle for the Indonesia’s independence.